Homesourcing ÃÂÃÂ¢ÃÂÃÂÃÂÃÂ The Best for Both Worlds of Employers and Employees - Ho, Siow Ping (2006)
The dissertation looks at homesourcing and the feasibility of it in Singapore. It looks at how homesourcing can benefit both employers and employees. Although there are companies which had implemented homesourcing, there are few and are mainly in the information technology industry. With the good information communication infrastructure and an educated and hardworking workforce in Singapore, there are advantages to encourage more homesourcing. The relatively high office rental rates in Singapore is another reason to encourage homesourcing, which also ties in nicely with the governmentÃÂÃÂ¢ÃÂÃÂÃÂÃÂs aim to promote Singapore as a shared services centre. Furthermore, the government has been active in promoting the importance and benefits of a friendly work-life culture and homesourcing could be a good solution.